2017
DOI: 10.3126/jpan.v5i1.18329
|View full text |Cite
|
Sign up to set email alerts
|

A study on EEG findings: An Experience from a Tertiary Care Center of Nepal

Abstract: Introduction: The electroencephalography (EEG) is the recording of brain's spontaneous electrical activity over a period of time (15)(16)(17)(18)(19)(20)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…10,14 Abnormal generalized epileptiform discharge was seen in 11% of our respondents. A study by Joshi revealed abnormal EEG in 43.3% with generalized epilepsy diagnosed on EEG in 26.21% 15 . Limitations of the study: Limitation of the study is that sample size was small and under six months infants were included, and was done only in two centers so we further recommend that further similar studies should be conducted in different settings with different protocols and include different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 Abnormal generalized epileptiform discharge was seen in 11% of our respondents. A study by Joshi revealed abnormal EEG in 43.3% with generalized epilepsy diagnosed on EEG in 26.21% 15 . Limitations of the study: Limitation of the study is that sample size was small and under six months infants were included, and was done only in two centers so we further recommend that further similar studies should be conducted in different settings with different protocols and include different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalogram (EEG) is a pivotal tool in neuroscience, facilitating the study of brain activity and behavior (Jiang et al, 2019). It entails the recording of brain electrical activity over a specific timeframe (Joshi & Shakya, 2017). However, it is important to note that EEG does not directly measure the real brain signal.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalogram (EEG) is a pivotal tool in neuroscience, facilitating the study of brain activity and behavior (Jiang et al, 2019). It entails the recording of brain electrical activity over a specific timeframe (Joshi & Shakya, 2017). However, it is important to note that EEG does not directly measure the real brain signal.…”
Section: Introductionmentioning
confidence: 99%